دراسة تأثير بعض الإضافات الغذائية على إنتاجية ديدان القز .Bombyx mori L Lepidoptera:Bombycidae).) - مكيس, خليل; العابد, تمام; عكاشة, إيمان (Latakia University Journal -Biological Sciences Series, 2018)
تعتبر دراسة تأثير بعض الإضافات الغذائية على إنتاجية ديدان القز مؤشراً علمياً وتطبيقياً من أجل إلقاء المزيد من الضوء على التربية الحديثة لدودة القز ورفع إنتاجيتها. فقد استخدم عسل النحل بتراكيز (0.25- 2%) و بينت النتائج أن التركيز 1.5% أعطى أعلى القيم من حيث طول ووزن الشرانق ومحتواها من الحرير. أما الغذاء الملكي فقد استخدم بتراكيز (0.25- 1.5%) وظهر أن التركيز 0.5% أعطى أفضل القيم من حيث طول ووزن الشرانق ومحتواها من الحرير والمشاقة ووزن العذراء عند إضافة مستخلص اليانسون بتراكيز (2 - 10%) أعطى التركيز 10% أفضل القيم من حيث طول وعرض الشرانق ووزن الشرانق ومشاقتها ووزن العذراء.بينما تبين عند إضافة خميرة الخبازين بتراكيز (1 - 8%) أن التركيز 4% أعطى أفضل القيم لعرض الشرنقة ووزنها ومحتواها من الحرير والمشاقة ووزن العذراء. Studying the influence of some supplementary nutrition on the production of silk worms is considered a scientific and applicant indicator, shedding lights on the modern breeding of silk worm, and increasing its productivity. Adding various concentrations (0.25- 1.5%) of bee honey showed that 1.5% of bee honey gave the best value in terms of length, weight, and silk content of the cocoons. Addition of various concentrations (0.5- 1.5%) of royal jelly showed that the concentration 0.5% gave the best values in terms of length, weight, and silk content of the cocoons and floss, and pupae weight. Addition of various concentrations (2-10%) of anise extract showed that the concentration 10% gave the best values in terms length, width, weight, of the cocoons and floss, and pupae weight. Addition of various concentrations (1-8%) of Baker's yeast showed that the concentration ( 4%) gave the best values in terms of width, weight, silk content of the cocoons and floss, and pupae weight.